Lecturers' and TESL teacher trainees' perceptions towards the level of readiness in performing teaching practice [electronic resource] - 278409 Shereena Sreetharam (Skudai : Universiti Teknologi Malaysia, 2008)
Project Paper (Sarjana Muda Sains serta Pendidikan (Pengajaran Bahasa Inggeris Sebagai Bahasa Kedua)) - Universiti Teknologi Malaysia, 2008